Transportation Model : Review of Its Practical Application in Kogi State, Nigeria - Audu Samson (International Journal of Applied and Scientific Research, 2024)
The transportation model is a linear programming model targeting at minimization of transportation cost for any firm. However, it is critical to examine how effective it can be applied to enable firms   pursue its immediate and strategic objectives. This study on transportation model is carried out to examine the practical application of transportation model in Otebu Investment limited Idah, Kogi State. The study was induced by the curiosity to ascertain the extent in which the transportation model as a branch of linear programming model is being applied by the firm and how this model has been able to enhance the performance through cost minimization. The study empirically reached both the Management, senior and junior employees of the enterprise through field descriptive survey research and finding revealed that the application of transportation model of linear programming have been able to enhance the performance of the firm hence considering the fact that there is a link between cost minimization and revenue drive of the Firms this model should be consistently adopted so as to be able to continuously minimize transportation cost.